Computer based instrumentation for level measurement using visual basic application - Mohd Hafiz, Hasbullah (2008)
Interfaces commonly used to connect computers to instruments system. It is not intended to be definitive, or very detailed, but to give the user an idea of what is readily achievable with the various systems. In this context, the study, research and system development will be focused on using GUI system as a medium to interface with the instrument part. There are several of GUI systems today but Visual Basic application will be use for this project. However, most of computer based instrumentation system widely use in industrial field compared to study field. The purpose of this project is to study the concept of computer based instrumentation system itself, redevelop the system just to make sure it’s more efficient and user friendly and to find the answer whether it’s suitable to be implement as a learning tools or not. As a result the system developed will be able to interface with the level measurement instrumentation and it can be a very useful learning tool for lab session of subject BEE 4523: Industrial Instrumentation. This system will reduce all the calculation hassle that might be face by the student and will reduce the calculation error because this system provide 100 % calculation made by the computer and the precision of graph should not be hesitate by the user.